2010
DOI: 10.1007/s00253-010-2587-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of acyl-coenzyme A carboxylase complex in lipstatin biosynthesis of Streptomyces toxytricini

Abstract: Streptomyces toxytricini produces lipstatin, a specific inhibitor of pancreatic lipase, which is derived from two fatty acid moieties with eight and 14 carbon atoms. The pccB gene locus in 10.6 kb fragment of S. toxytricini chromosomal DNA contains three genes for acyl-coenzyme A carboxylase (ACCase) complex accA3, pccB, and pccE that are presumed to be involved in secondary metabolism. The pccB gene encoding a β subunit of ACCase [carboxyltransferase (CT)] was identified upstream of pccE gene for a small prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…First, the acyl-CoA synthetase homologue LstC might catalyze the ATP-dependent activation of octanoic acid to produce an acyl-CoA thioester via an acyl-adenylate intermediate (46). The octanoyl-CoA ester is then carboxylated to give hexylmalonyl-CoA, probably by an acyl-CoA carboxylase (ACCase) complex, the inactivation of which caused a decrease of lipstatin production by ϳ80% in S. toxytricini (30). An unknown route may be present to complement the ACCase pathway for the generation of hexylmalonyl-CoA, however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the acyl-CoA synthetase homologue LstC might catalyze the ATP-dependent activation of octanoic acid to produce an acyl-CoA thioester via an acyl-adenylate intermediate (46). The octanoyl-CoA ester is then carboxylated to give hexylmalonyl-CoA, probably by an acyl-CoA carboxylase (ACCase) complex, the inactivation of which caused a decrease of lipstatin production by ϳ80% in S. toxytricini (30). An unknown route may be present to complement the ACCase pathway for the generation of hexylmalonyl-CoA, however.…”
Section: Discussionmentioning
confidence: 99%
“…S. toxytricini strains were grown on International Streptomyces Project Medium 4 (ISP4; BD Biosciences, San Jose, CA, USA) for sporulation and conjugation. Fermentation seed medium (10 g of soya bean flour, 5 g of Bacto soytone, 5 ml of glycerol, 10 ml of soya oil, and 2 ml of Triton X-100 [pH 6.5] per liter) and fermentation medium (30 g of soya bean flour, 14 ml of glycerol, 1 g of Bacto soytone, 1 ml of Triton X-100, and 60 ml of soya oil [pH 7.0] per liter) (30) were used for shake flask fermentation of S. toxytricini and S. lividans strains.…”
Section: Methodsmentioning
confidence: 99%
“…Linoleic acid contains the same number of double bonds as lipstatin chain and it is the basic building unit. Further experiments with feeding putative intermediates in the process of fermentation indicated that linoleic acid, caprylic acid and N-formyl-L-leucine or preferably L-leucine are effective precursors of lipstatin biosynthesis (Schuhr et al, 2002;Eisenreich et al, 2003;Demirev et al, 2010).…”
Section: Full Papermentioning
confidence: 99%
“…In S. toxytricini, the acetylCoA carboxylase gene cluster is the pccB gene locus containing accA3, pccB, and pccE, which has been demonstrated to be involved in the secondary metabolism. Disruption of the pccB and pccE genes caused a lipstatin production reduction as much as 80%, indicating their critical role in lipstatin biosynthesis (Demirev et al, 2009(Demirev et al, , 2010. The pccB gene encodes a β subunit of ACCase functioning as carboxyltransferase in the activation of ACCase along with biotinylation mediated by Bp1 protein, which needs divalent cations as a cofactor (Demirev et al, 2011).…”
Section: Full Papermentioning
confidence: 99%
See 1 more Smart Citation